G-Quadruplex-Based Drug Delivery Systems for Cancer Therapy - Lopes-Nunes, Jéssica (Pharmaceuticals (Basel), 2021)
G-quadruplexes (G4s) are a class of nucleic acids (DNA and RNA) with single-stranded G-rich sequences. Owing to the selectivity of some G4s, they are emerging as targeting agents to overtake side effects of several potential anticancer drugs, and delivery systems of small molecules to malignant cells, through their high affinity or complementarity to specific targets. Moreover, different systems are being used to improve their potential, such as gold nano-particles or liposomes. Thus, the present review provides relevant data about the different studies with G4s as drug delivery systems and the challenges that must be overcome in the future research.